QUALITY TEST OF WHITE TEAK (Gmelina arborea) AND CANDLENUT (Aleurites moluccana) SEEDLINGS IN THE BPDAS-HL BONE BOLANGO PERMANENT NURSERY - Djafar, Rilan; Puspaningrum, Dian; Ernikawati, Ernikawati (Universitas Gorontalo, 2024)
ABSTRACTIndonesian National Standard (SNI) No. 8420 of 2018 concerning forest plant seeds is a reference for determining the quality of quality seeds. Technical instructions for assessing the quality of forest plant seeds by Regulation of the Director General of Land Rehabilitation and Social Forestry (RLPS) number P.05/V-SET/2009. Gmelina arborea and Aleurites moluccana seeds are priority seeds for production and use in RHL activities, so research focuses on these two types. The study aimed to determine the quality of Gmelina arborea and Aleurites moluccana seeds produced by the BPDAS-HL Bone Bolango Permanent Nursery. Data collection was carried out by selecting the sample using the Systematic Sampling with Random Start method based on SNI sampling requirements. There were 19,800 Gmelina arborea seeds and 5,900 Aleurites moluccana seeds with a sampling intensity of 0.2%. Testing for Gmelina arborea showed poor results in contrast to Aleurites moluccana in terms of percentage: Media compactness of the two types tested produced a percentage of 100% of the Aleurites moluccana type and 73.5% of the Gmelina arborea type. Seedling height, from the test percentages for both types, produces a percentage of 100%. For seed diameter, the Gmelina arborea test produced a value of 91%, and the Aleurites moluccana type produced a value of 100%. The percentage of leaves for the Gmelina arborea type is 45%, while the percentage for the Aleurites moluccana type is 100%. Average special requirements (RPK), the Gmelina arborea type produces a percentage of 77.37% while the Aleurites moluccana type produces a percentage of 100%. The test results (final score) resulted in 68 Gmelina arborea seedlings that fell into the first criterion (P), 120 in the second criterion (D) and 12 that did not pass the test (X). Meanwhile, the Aleurites moluccana type produces a percentage of 100% which is in the first quality (P).Keywords: Quality Testing; Seedlings; SNI; BPDASHL; Bone-Bolango.